Tumor-targeting oncolytic virus elicits potent immunotherapeutic vaccine responses to tumor antigens. (1st January 2020) - Luo, Yong; Lin, Chaolong; Zou, Yidi; Ju, Fei; Ren, Wenfeng; Lin, Yanhua; Wang, Yale; Huang, Xiaoxuan; Liu, Huiling; Yu, Zeng; Liu, Pingguo; Tan, Guowei; et al.
ABSTRACT: Oncolytic viruses represent a promising therapeutic modality, but they have yet to live up to their therapeutic potential. Safety and efficacy concerns impel us to identify least toxic oncolytic agents that would generate durable and multifaceted anti-tumor immune responses to disrupt the tumors. Here we describe a rational engineered oncolytic herpes virus (OVH) that is a selective killer for targeting tumors, has strong safety records, induces complete regression of tumors in multiple tumor models, and elicits potent antitumor immunity. By far, the potential of OVs in promoting the tumor antigen-specific humoral immune responses remains obscure. In this study, we found that effective treatment by OVH induced immunogenic cell death, which facilitates to elicit humoral immune responses. Depletion experiments revealed that B cells were required for maximal antitumor efficacy of oncolytic immunotherapy. Both serum transfer and antibody treatment experiments revealed that endogenous oncolysis-induced antigen-targeting therapeutic antibodies can lead to systemic tumor regression. Our data demonstrate that tumor-targeting immune modulatory properties confer oncolytic OVH virotherapy as potent immunotherapeutic cancer vaccines that can generate speciﬁc and efﬁcacious antitumor humoral responses by eliciting endogenous tumor antigen-targeting therapeutic antibodies in situ, resulting in an efficacious and tumor-specific therapeutic effect.